Lower spinal postural variability during laptop-work in subjects with cervicogenic headache compared to healthy controls - Mingels, Sarah; Dankaerts, Wim; van Etten, Ludo; Bruckers, Liesbeth; Granitzer, Marita (Scientific reports, 2021)
Spinal postural variability (SPV) is a prerequisite to prevent musculoskeletal complaints during functional tasks. Our objective was to evaluate SPV in cervicogenic headache (CeH) since CeH is characterized by such complaints. A non-randomized repeated-measure design was applied to compare SPV between 18 participants with reporting CeH aged 29–51 years, and 18 matched controls aged 26–52 years during a 30-min-laptop-task. Habitual spinal postures (degrees) of the cervical, thoracic and lumbar spine were analysed using 3D-Vicon motion analysis. SPV, to express variation in mean habitual spinal posture, was deducted from the postural analysis. Mean SPV of each spinal segment was lower in the CeH-group compared to the control-group. Within the CeH-group, SPV of all except one spinal segment (lower-lumbar) was higher compared to the group’s mean SPV. Within the control-group, SPV was more comparable to the group’s mean SPV. SPV differed between groups. Averaging data resulted in decreased SPV in the CeH-group compared to the control-group during the laptop-task. However, the higher within-group-SPV in the CeH-group compared to the group’s mean SPV accentuated more postural heterogeneity. It should be further determined if addressing individual SPV is a relevant intervention.